2020
DOI: 10.1016/j.physa.2019.123417
|View full text |Cite
|
Sign up to set email alerts
|

On the order of the phase transition in the spin-1 Baxter–Wu model

Abstract: In this work we investigate the order of the phase transition of the spin-1 Baxter-Wu model. We used extensive entropic simulations to describe the behavior of quantities which reveal the order of the phase transition. We applyied finite-sizing scaling laws for continuous and discontinuous phase transitions. Our results show that this system exhibits an indeterminacy regarding the order of the phase transition, i.e., the results are conclusive for both transitions, whether continuous or discontinuous. In such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 45 publications
(52 reference statements)
3
17
0
Order By: Relevance
“…However, this double peak characteristic can be a finite-size effect and, a more detailed study in this region is still missing. For positive values of the field, the finite-size effect will not remove the two peaks, since we have for the case D = 0.0 the presence of these two peaks at the thermodynamic limit [10] and one can see that the greater the crystal field, the larger the separation between the two peaks. Therefore, we might conclude that the secondorder critical line is a line of tetracritical points.…”
Section: Entropic Sampling Simulations With the Joint Density Of Statesmentioning
confidence: 81%
See 4 more Smart Citations
“…However, this double peak characteristic can be a finite-size effect and, a more detailed study in this region is still missing. For positive values of the field, the finite-size effect will not remove the two peaks, since we have for the case D = 0.0 the presence of these two peaks at the thermodynamic limit [10] and one can see that the greater the crystal field, the larger the separation between the two peaks. Therefore, we might conclude that the secondorder critical line is a line of tetracritical points.…”
Section: Entropic Sampling Simulations With the Joint Density Of Statesmentioning
confidence: 81%
“…Ref. 24 demonstrated that when using the order parameter as the total magnetization, one can consider systems with non-multiple of three lattice sizes without loss of generality of the model [10]. Thus we ran simulations for L = 8, 10, 14, and 16 with n = 24, 20, 20, and 16 independent runs, respectively.…”
Section: Entropic Sampling Simulations With the Joint Density Of Statesmentioning
confidence: 99%
See 3 more Smart Citations